Monev Hasil Lomba Krenova dan Hilirisasi Riset Perguruan Tinggi Tahun 2017-2022 - M Edwin Zulfikar Atmani W; Wahyu Hermawan (Badan Riset dan Inovasi Daerah Kota Surakarta, 2023)
Sustainable regional development requires directed and integrated guidance, development and innovation efforts to create competitiveness. The higher the level of competitiveness of a region, the higher the level of welfare of its people. The Surakarta City Government has established a strategy to increase competitiveness, including by holding various competitions. The Krenova and Downstream Research Competition has been regularly held except in 2020 due to the pandemic factor. The number of participants is increasing by utilizing social media in their outreach. However, based on initial observations, there has not been continuous business incubation so that participant development data cannot be monitored. Currently it is not known for certain how the downstreaming of Higher Education Research and Business development from the Krenova Competition will develop. This consideration is the reason for the need to hold monitoring and evaluation of the Krenova Competition and Downstreaming of Higher Education Research Results in 2023.